2021
DOI: 10.1002/jcop.22505
|View full text |Cite
|
Sign up to set email alerts
|

The national identity on the border: Indonesian language awareness and attitudes through multi‐ethnic community involvement

Abstract: State borders are the areas that are vulnerable to the degradation of national identity. The purpose of this study was to investigate the attitudes and the behavior of language use among the multi-ethnic Indonesian of predominantly Dayak, Malay, and Chinese who resided on the Indonesia-Malaysia border. The present research applied a qualitative ethnographic approach to document and to describe how a group of multi-ethnic communities participated in building their awareness, attitudes and practices of language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…In addition, the family environment is an important factor that can support the formation of nationalism character [50] in IMW's children in border areas, because the family is the first place to learn about Indonesia. Meanwhile, the social environment is a diverse community so there needs to be awareness and seriousness in maintaining national identity through the use of Indonesian language in social interactions, this can reflect the realization of the nationalist attitude of each individual in the border area [51].…”
Section: The Experience On Nationalismmentioning
confidence: 99%
“…In addition, the family environment is an important factor that can support the formation of nationalism character [50] in IMW's children in border areas, because the family is the first place to learn about Indonesia. Meanwhile, the social environment is a diverse community so there needs to be awareness and seriousness in maintaining national identity through the use of Indonesian language in social interactions, this can reflect the realization of the nationalist attitude of each individual in the border area [51].…”
Section: The Experience On Nationalismmentioning
confidence: 99%
“…In other words, there is a trend toward national language dominance at the expense of the indigenous language. A number of studies have shown that indigenous languages in Indonesia are constantly under threat from other languages, such as Indonesian, which has been designated as the country's official language by the government (Abtahian et al, 2016;Dirgeyasa, 2016;Martin-Anatias, 2018;Martono et al, 2022;Simanjuntak, 2017;Siregar, 2022). Thus, as a multilingual nation, Indonesia has a challenge in preserving the indigenous language.…”
Section: Production Of Equivalentsmentioning
confidence: 99%
“…Keberagaman etnik tradisional (Martono, et al, 2021) telah membawa Indonesia masuk dalam lima besar negara di dunia yang memiliki beragam warisan budaya (Ayu, 2017). Berbagai upaya telah dilakukan oleh pemerintah Indonesia serta para aktivis pemerhati budaya dalam upaya pelestarian budaya dan nilai-nilainya.…”
Section: Nilai Warisan Budaya Tak Benda Pada Pamole Beounclassified